Carbon nanotubes/β-cyclodextrin/MnFe2O4 as a magnetic nanocomposite powder for tetracycline antibiotic decontamination from different aqueous environments. Issue 6 (December 2021) - Foroutan, Rauf; Peighambardoust, Seyed Jamaleddin; Latifi, Parvaneh; Ahmadi, Amir; Alizadeh, Mehran; Ramavandi, Bahman
Abstract: In this work, carbon nanotubes (CNT) and β-cyclodextrin (CD) was used to generate magnetic composites (CNT/MnFe2 O4 and CNT/β- CD/MnFe2 O4 ) to remove the emerging contaminant of tetracycline (TC) antibiotic from various aqueous solutions. Various techniques were used to investigate the structural and surface characteristics of the adsorptive composites. Brunauer–Emmett–Teller (BET) test illustrated that the synthesized magnetic composites have a higher specific active surface than CNT. The effect of water pH, temperature, sorption time, TC content, and type of aqueous solution on the elimination efficiency was explored. Our data followed the isotherm models of Redlich-Peterson and Temkin. The peak of TC adsorption capacity from distilled water using CNT, CNT/MnFe2 O4, CNT/β-CD/MnFe2 O4 was determined 82.66 mg/g, 86.48 mg/g, and 89.53 mg/g, respectively. The TC adsorption capacity using CNT/β-CD/MnFe2 O4 magnetic composite from urban drinking water and wastewater was determined at 55.02 mg/g and 40.36 mg/g, respectively. The adsorption process revealed that the removal of TC from distilled water using the synthesized adsorbents follows the pseudo-first-order model. In contrast, the removal of TC from municipal drinking water and wastewater follows the pseudo-second-order kinetic model. The TC decontamination process was spontaneous and exothermic and could be performed well at ambient temperature. Overall, the studied adsorbents (CNT and CNT-based magnetic composites) can be used as promising adsorbents in the TC removal processes from aqueous solutions. Graphical Abstract: ga1 Highlights: The CNT/β-Cyclodextrin/MnFe2 O4 nanocomposite had a BET value of 166 m 2 /g. Tetracycline (TC) from different solutions was adsorbed to the magnetic composite. The TC uptake capacity from wastewater using nanocomposite was obtained 40 mg/g. The TC adsorption onto nanocomposite followed Redlich-Peterson and Temkin models. The TC removal from distilled water was obeyed pseudo-first-order model.